A study of safe CO2 storage capacity in saline aquifers: a numerical study. (1st October 2012) - Ranjith, P.G.; Perera, M.S.A.; Khan, E.
SUMMARY An effective way of reducing greenhouse gas content in the atmosphere is carbon dioxide (CO2) geo‐sequestration in saline aquifers. The main objective of this study is to develop a 3‐D numerical model to identify the optimum CO2 storage capacity in saline aquifers by studying the factors affecting it and the possibility of the injected CO2 back‐migrating into the atmosphere. A 1000m×1000m×184 m saline aquifer, lying 800 m below the ground surface, was therefore considered to develop a model using the COMET 3 reservoir simulator. The effects of injecting CO2 properties (injection pressure) and the aquifer's properties (depth, temperatures and salinity) on the CO2 storage capacity were examined first. According to the results of the model, CO2 storage capacity increases with increasing injection pressure and salinity and decreasing depth and temperature, and 100% variations in injection pressure, depth, temperature and salinity levels cause the CO2 storage capacity to be changed by 54%, 36%, 18% and 1.8%, respectively. The next stage of the study involved the determination of cap rock failure due to CO2 injection pressure and the identification of the factors influencing it. A detailed parametric study was conducted, with changes to the depth, temperature and salinity with respect to injection pressure, to detect the effects of these factors on the optimum CO2 injection pressure. According to the results, optimum CO2 injection pressure clearly depends on the aquifer depth and the effects of salinity and temperature are negligible. An increment of 0.8 to 1.4 km in aquifer depth causes the optimum injection pressure to be increased from 19.55 to 42 MPa, which is about 105 and 107 higher than the effects of temperature (20 to 110 °C increment) and salinity level (100, 000 to 160, 000 ppm increment), respectively. The model can be used effectively in field studies to safely enhance CO2 storage capacity in saline aquifers. Copyright © 2012 John Wiley & Sons, Ltd.